2005
DOI: 10.1111/j.1570-7458.2005.00271.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses in three ichneumonid pollen beetle parasitoids to volatiles emitted from different phenological stages of oilseed rape

Abstract: Pollen beetles ( Meligethes spp.; Coleoptera: Nitiduliae) are a major pest of oilseed rape, Brassica napus L. (Brassicaceae) in northern Europe. Phradis interstitialis Thomson, P. morionellus Holmgr., and Tersilochus heterocerus Thomson (Hymenoptera: Ichneumonidae) are among the most frequent pollen beetle parasitoids. These three species differ in temporal occurrence, as well as in preferred host stage. The behavioural responses of female parasitoids to odours from oilseed rape at bud and flowering stage were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
53
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(54 citation statements)
references
References 46 publications
1
53
0
Order By: Relevance
“…Olfactometer studies found that the three main species of pollen beetle parasitoid were all attracted to volatiles from OSR in the bud stage; however, there was an interesting finding of niche separation between the three competing species as they each displayed preferences for volatiles from insect infestations at different stages of OSR development that corresponded to their preferred host growth stage (Jonsson et al 2005;Berger et al 2015). After landing on the host-plant, T. heterocerus female parasitoids have also been shown to be attracted to volatiles from their pollen beetle host larvae (Straka et al 2013;Berger et al 2015).…”
Section: Predation By Natural Enemiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Olfactometer studies found that the three main species of pollen beetle parasitoid were all attracted to volatiles from OSR in the bud stage; however, there was an interesting finding of niche separation between the three competing species as they each displayed preferences for volatiles from insect infestations at different stages of OSR development that corresponded to their preferred host growth stage (Jonsson et al 2005;Berger et al 2015). After landing on the host-plant, T. heterocerus female parasitoids have also been shown to be attracted to volatiles from their pollen beetle host larvae (Straka et al 2013;Berger et al 2015).…”
Section: Predation By Natural Enemiesmentioning
confidence: 99%
“…Ideally, this should be a 'dead-end' trap crop (Shelton and Badenes-Perez 2006) such as Raphanus sativus (L.) Domin (Veromann et al 2014). Biological control of the pollen beetles in the trap crop could be enhanced by attracting natural enemies using attractant lures based on host-plant volatiles (Jonsson et al 2005;Jöns-son and Anderson 2007) or volatiles from their host larvae (Straka et al 2013;Berger et al 2015), but this concept is still in the early research phase. As the push component, volatiles from lavender essential oil (Lavandula angustifolia) were found to be effective in deterring pollen beetles in laboratory bioassays (Mauchline et al 2005(Mauchline et al , 2008 and in both semi-field and field trials (Mauchline et al 2013).…”
Section: The Push-pull Systemmentioning
confidence: 99%
“…Phradis interstitialis Thomson, Phradis morionellus Holmgr. and Tersilochus heterocerus Thomson are among the most frequent pollen beetle parasitoids (Jönsson et al, 2005). Among these three parasitoids, the parasitoid P. morionellus attacks larvae inside oilseed rape buds and flowers and also feeds on the flowers (Jönsson and Anderson, 2007 and references therein).…”
Section: Parasitoids or Predatorsmentioning
confidence: 99%
“…The attraction to the most effective unbaited yellow traps was enhanced 1.7-3.3 times with the addition of a lure comprising a mixture of allyl, 3-butenyl, 4-pentenyl and 2-phenylethyl isothiocyanate. Jönsson et al (2005) analysed behavioural responses in three ichneumonid pollen beetle (M. aeneus) parasitoids (P. interstitialis, P. morionellus and T . heterocerus) to volatiles emitted from different phenological stages of oilseed rape.…”
Section: Plants (Brassica Spp)-herbivores (Phyllotreta Spp and Melimentioning
confidence: 99%
“…While earlier literature suggested that this happens by random walking, host finding can be better understood by the search for physical and chemical cues of host presence, under the assumption that a parasitoid using such cues would have a reproductive advantage over parasitoids that search randomly (Vinson, 1976;Casas, 2000). For pollen beetle parasitoids, there is evidence for the use of OSR odors and visual stimuli: Jönsson et al (2005) found that P. morionellus avoided odors of flowering OSR and was attracted to bud odors similarly to P. interstitialis, while T. heterocerus was attracted to flower stimuli. This suggests that P. morionellus and T. heterocerus differ more than was supposed by earlier workers, and that the host and plant stage preferences of these three related species deserve closer attention.…”
Section: Introductionmentioning
confidence: 99%